2015
DOI: 10.1002/2014je004710
|View full text |Cite
|
Sign up to set email alerts
|

Dielectric breakdown weathering of the Moon's polar regolith

Abstract: Galactic cosmic rays and solar energetic particles (SEPs) can charge the Moon's subsurface, a process expected to be particularly important in the polar regions. Experiments have shown that sufficient fluences (i.e., time‐integrated fluxes) of energetic charged particles can cause dielectric breakdown, in which the electric field rapidly vaporizes small, filamentary channels within a dielectric. Lunar regolith has both the characteristics and, in some polar locations, the environment needed to make breakdown l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(20 citation statements)
references
References 54 publications
0
20
0
Order By: Relevance
“…Because PSRs are so different than other planetary environments, they contain a wide range of fascinating effects, processes, and targets of scientific study. In addition to volatile enhancements, other interesting attributes about PSRs include unique surface charging and space plasma physics effects [ Zimmerman et al ., ; Jordan et al ., ; Farrell et al ., ], potentially distinctive geotechnical properties of the persistently cold and volatile‐rich regolith [ Schultz et al ., ], and the possible organic synthesis that may take place within PSR volatiles due to long‐term cosmic ray bombardment [ Crites et al ., ]. Because of their unique nature, PSRs can be difficult to study, and even now in the early 21st century there are many fundamental aspects of PSRs that are not understood.…”
Section: Introductionmentioning
confidence: 99%
“…Because PSRs are so different than other planetary environments, they contain a wide range of fascinating effects, processes, and targets of scientific study. In addition to volatile enhancements, other interesting attributes about PSRs include unique surface charging and space plasma physics effects [ Zimmerman et al ., ; Jordan et al ., ; Farrell et al ., ], potentially distinctive geotechnical properties of the persistently cold and volatile‐rich regolith [ Schultz et al ., ], and the possible organic synthesis that may take place within PSR volatiles due to long‐term cosmic ray bombardment [ Crites et al ., ]. Because of their unique nature, PSRs can be difficult to study, and even now in the early 21st century there are many fundamental aspects of PSRs that are not understood.…”
Section: Introductionmentioning
confidence: 99%
“…If the fragmented grains are small enough that van der Waals forces can overcome gravity, then high‐porosity fairy‐castle structures could be formed in the upper regolith (Hapke & Horn, ). Because the frequency of dielectric breakdown is temperature dependent (higher frequency at lower temperatures; Jordan et al, ), and the lowest albedos observed by LAMP correlate with cold polar PSRs, this process may explain the low albedos seen in Amundsen's PSRs.…”
Section: Discussionmentioning
confidence: 99%
“…The incident high-energy protons of SEPs (∼MeV) may cause dielectric breakdown of the lunar regolith, in particular in the shadowed regions inside the polar craters (Jordan et al 2015(Jordan et al , 2017Jordan 2021). The dielectric breakdown may alter the porosity of the subsurface (∼1 mm), facilitating vaporization of volatile elements in the regolith.…”
Section: Space Weatheringmentioning
confidence: 99%